Resistance against and collusion with colonialism: Eileen Chang’s writing and translation of “Steamed Osmanthus Flower Ah Xiao’s Unhappy Autumn” - Qiao Meng,; Omar, Noritah (Universiti Putra Malaysia Press, 2012)

(untitled)
Despite rising to stardom with her brilliant writings in Shanghai in the 1940s, Eileen Chang was criticised by the Leftist writers of her time and other later critics for failing to represent the general political panorama in China. In fact, they studied her works only with regard to the relations between her and China, but ignored the relationship between her, a writer of a semi-colonised nation, and the colonisers. However, through the analysis of her Chinese short story “Steamed Osmanthus Flower Ah Xiao’s Unhappy Autumn” (1944) and her own translation of it into English nentitled “Shame, Amah!” (1962) after her migration to the United States, this study explores how Chang resists colonialism through various means in the original text, and how such resistance is largely changed to collusion in the translation. The comparison between the source text and the translation reveals the dilemma of the diasporic writer - under the powerful domination of the host society, assimilation is inevitable; but at the same time, the writer is also trying hard to hold on to his or her own cultural traces.